Impact of the Gastric Acid Suppressant Use on the Safety and Effectiveness of EGFR-TKIs: A Systematic Review and Meta-Analysis - Du, Xin; Liu, Wei; Chen, Ken; Wang, Ziyu; Li, Xinyi; Yang, Li; Xie, Xiaohui (Frontiers in Pharmacology, 2022)
Background The use of gastric-acid suppressants (GASs) has an influence on the exposure of some epidermal growth factor receptor- tyrosine kinase inhibitor (EGFR-TKIs), and therefore may affecting the effectiveness and safety of EGFR-TKIs. The impact of GASs, including proton pump inhibitors (PPIs) and histamine type 2 receptor antagonists (H2RAs), on the effectiveness and safety of EGFR-TKIs remains unclear. We conducted a meta-analysis to explore the impact of GASs on the effectiveness and safety of EGFR-TKIs in Non-small cell lung cancer (NSCLC) patients. Method We searched the PubMed, Embase, Cochrane Library, China National Knowledge Infrastructure and Wanfang database thoroughly from inception to 2nd February 2021. Including the studies for NSCLC patients who using GASs, offering adjusted hazard ratio (HR) of effectiveness outcomes such as overall survival (OS) and progression-free survival (PFS) or adjusted odds ratio (OR) of the adverse drug reaction (ADR) and the results were calculated with a random effect. Two researchers independently screened the literature, extracted data, and evaluated the quality. Stata 15.0 were used for meta-analysis. Result Twelve studies were finally included. Nine of them were cohort studies and 3 of them were case-control studies. For effectiveness outcomes, the use of GASs was associated with shorter PFS (HR 1.66 [1.40,1.98]) and OS (HR 1.50 [1.31,1.72]) and the use of PPIs was associated with shorter OS (HR 1.56 [1.21,2.02]) regardless of the overlap time. For safety, the use of GASs (OR 1.98 [1.19,3.31]) or PPIs (OR 1.91 [1.17,3.12]) were both associated with hepatotoxicity. Conclusion The use of GASs is associated with a worse effectiveness, especially for PPIs, it’s also associated with a higher risk of hepatotoxicity. The co-administration of GAS should be avoided, if cannot be avoided, H2RAs is a better choice.